ESKALASI KOMITMEN TERHADAP PROYEK-PROYEK YANG TIDAK MENGUNTUNGKAN : PENGARUH LATAR BELAKANG PENDIDIKAN DAN PENGUNGKAPAN INFORMASI SEBAGAI PEMODELAN VARIABEL - Hari Sulistiyo (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
This study aims whether the variable framing is able to moderate the relationship between the variable Educational Background with Commitment Escalation Variables. This study also wants to find out whether the background of a manager (who understands Accounting VS who understands Management) has differences in making decisions about the continuation of unfavorable projects. . In addition, this study will also see whether the decision to proceed or not unprofitable projects can be moderated by framing. This study uses an experimental design, with 2 x 2 factorial, using the Anova test. The independent variable (factors) is the framing of negative and positive decision choices and educational background. Subjects who participated in this experiment were 80 people grouped into two groups. Subjects originating from the S1 Accounting Study Program at the Singapore University of Karawang (UNSIKA) consisted of 40 people, while students from the S1 Management Study Program of the Singapore University of Karawang (UNSIKA) were taken as many as 40 people. The results of this study indicate that partially educational background is able to influence commitment escalation, on the other hand, although framing partially has not been able to influence commitment escalation, framing is able to be a pure moderator for the relationship between Educational background variables and Commitment Escalation Variables.